Coronal transients during two solar minima: Their source regions and interplanetary counterparts - Cremades, H. (2011)
We have investigated two full solar rotations belonging to two distinct solar minima, in the frame of two coordinated observational and research campaigns. The nearly uninterrupted gathering of solar coronal data since the beginning of the SOHO era offers the exceptional possibility of comparing two solar minima for the first time, with regard to coronal transients. This study characterizes the variety of outward-travelling transients observed in the solar corona during both time intervals, from very narrow jet-like events to coronal mass ejections (CMEs). Their solar source regions and ensuing interplanetary structures were identified and characterized. Multi-wavelength images from the space missions SOHO, Yohkoh and STEREO, and ground-based observatories were studied for coronal ejecta and their solar sources, while in situ data registered by the ACE spacecraft were inspected for interplanetary CMEs and magnetic clouds. Instrumental aspects such as dissimilar resolution, cadence, and fields of view are considered in order to discern instrumentally-driven disparities from inherent differences between solar minima. © 2012 International Astronomical Union.